Salt Appetite and its Effects on Cardiovascular Risk in Primary Aldosteronism - Adolf, Christian; Schneider, Holger; Heinrich, Daniel A.; Handgriff, Laura; Reincke, Martin (Hormone and Metabolic Research, 2020)
First described in 1955 by Jerome W. Conn, primary aldosteronism (PA) today is well established as a relevant cause of secondary hypertension and accounts for about 5–10 % of hypertensives. The importance of considering PA is based on its deleterious target organ damage far beyond the effect of elevated blood pressure and on PA being a potentially curable form of hypertension. Aside the established contributory role of high dietary salt intake to arterial hypertension and cardiovascular disease, high salt intake is mandatory for aldosterone-mediated deleterious effects on target-organ damage in patients with primary aldosteronism. Consequently, counselling patients on the need to reduce salt intake represents a major component in the treatment of PA to minimize cardiovascular damage. Unfortunately, in PA patients salt intake is high and far beyond the target values of 5 g per day, recommended by the World Health Organization. Insufficient patient motivation for lifestyle interventions can be further complicated by enhancing effects of aldosterone on salt appetite, via central and gustatory pathways. In this context, treatment for PA by adrenalectomy results in a spontaneous decrease in dietary salt intake and might therefore provide further reduction of cardiovascular risk in PA than specific medical treatment alone. Furthermore, there is evidence from clinical studies that even after sufficient treatment of PA dietary salt intake remains a relevant prognostic factor for cardiovascular risk. This review will focus on the synergistic benefits derived from both blockade of aldosterone-mediated effects and reduction in dietary salt intake on cardiovascular risk.
Keywords: salt intake; oxidative stress; aldosterone